Kewenangan Kejaksaan Penghentian Penuntutan dalam Perkara Pidana Berdasarkan Restorative Justice - Yuspar Yuspar (LPPM Universitas Ekasakti Padang, 2023)
Criminal cases, both large and small cases or serious and minor cases, are all resolved through a judicial mechanism which results in imprisonment, as a result of overcapacity in prison, apart from that the convict and the victim still have dissatisfaction, of course, other alternatives to consider such as the concept of restorative justice . The restorative approach is a process of solving criminal acts that aims to restore the situation to its original state. The Attorney General's Office as an institution that is given the authority in terms of prosecution in criminal cases, of course, is also given the authority to terminate criminal cases, through the Regulation of the Attorney General of the Republic of Indonesia number 15 of 2020 concerning Cessation of Prosecution based on Restorative Justice, it can be possible for cases that comply with the criteria in the regulation.